Stimulating The Role of Civil Societies for Sustainable Development Through Social Entrepreneurship - eunadenuga, , Ademoluoluwas (International Journal of Psychosocial Rehabilitation, 2020)
Civil Societies (CS) in Nigeria perform multifaceted functions towards societal sustainability ranging from advocacy for good governance to better welfarism for the citizenry. But despite these efforts, several CS end up in extinction with reasons mainly attributed to sustainability challenges. Hence, it is imperative to investigate the impediments to the existence of Nigerian civil societies; examine the source of Nigerian CS income with a view of assessing their coping strategies in an effort to incorporate Schumpeter’s Social entrepreneurship theory to the sustenance of CS in Nigeria. The study explored descriptive research design. The study utilized primary data and secondary data. Six civil society organizations in Nigeria were purposively selected for the study. The primary data was retrieved through phone interviews and Key informant interview while the secondary data involved extensive review of relevant literature. The primary data were analysed using content analysis. Findings revealed that lack of guaranteed source of regular income, poor human resource management and lack of incentive for volunteers of CS were largely responsible for the dearth of viable and vibrant CS; several CS relied heavily on mono-donors for funding and when such donors withdraw support it seriously affect the existence and activities of the CS; and very few CS have adopted social entrepreneurship as a coping strategy. The study concluded that more CS in Nigeria will still continue to become extinct until a stable and consistent source of income is guaranteed. Social entrepreneurship, therefore, is recommended for the Nigerian CS to maintain their momentum and continually guarantee sustainable development in their respective fields. Keywords–, ,